Aerodynamic Analysis on Wind Turbine Aerofoil - ., Albi; Dev Anand, M; M. Joselin Herbert, G (International Journal of Engineering and Technology, 2018)
The aerofoils of wind turbine blades have crucial influence on aerodynamic efficiency of wind turbine. There are numerous amounts of research being performed on aerofoils of wind turbines. Initially, I have done a brief literature survey on wind turbine aerofoil. This project involves the selection of a suitable aerofoil section for the proposed wind turbine blade. A comprehensive study of the aerofoil behaviour is implemented using 2D modelling. NACA 4412 aerofoil profile is considered for analysis of wind turbine blade. Geometry of this aerofoil is created using GAMBIT and CFD analysis is carried out using ANSYS FLUENT. Lift and Drag forces along with the angle of attack are the important parameters in a wind turbine system. These parameters decide the efficiency of the wind turbine. The lift force and drag force acting on aerofoil were determined with various angles of attacks ranging from 0° to 12° and wind speeds. The coefficient of lift and drag values are calculated for 1×105 Reynolds number. The pressure distributions as well as coefficient of lift to coefficient of drag ratio of this aerofoil were visualized. The CFD simulation results show close agreement with those of the experiments, thus suggesting a reliable alternative to experimental method in determining drag and lift.